The Importance of Preventive Measures to Reduce the Incidence of Postpartum Depression in Unintended Pregnancies: A Narrative Review - Sujiyatini Sujiyatini; Abdul Ghofur; Ana Kurniawati; Sari Hastuti; Supatmi (Jurnal Penelitian Pendidikan IPA, 2023)
Unintended pregnancies and associated emotional issues can negatively affect expectant mothers, potentially harming both them and their babies. This study focuses on the significance of forgiveness as an intervention for healing emotional wounds, enhancing self-acceptance, and improving overall well-being and relationships among mothers. It assesses forgiveness's impact on the physical, psychological, social, and spiritual health of mothers throughout their lives, bolstering their resilience. A narrative review of evidence on forgiveness in the context of unwanted teenage pregnancies was conducted from January 2016 to January 2019, including PubMed, EMBASE and Cochrane, EBSCO, PubMed, UpToDate, and Clinical Key. Out of 995 studies, 14 articles were selected, primarily emphasizing forgiveness therapy for adolescent bullying and social issues. Although research on forgiveness in unwanted pregnancies was limited and had methodological limitations, early interventions are crucial to safeguard pregnant women's physical and mental health during pregnancy, childbirth, and the postpartum period. Further research with improved methodology is needed to comprehensively understand forgiveness's impact and enhance support for pregnant women